Phosphate rock fertilization in tilled and no-till low-input systems in the humid tropics - Gichuru, M.P.; Sanchez, P.A. (1988)
Effects of Sechura phosphate rock and superphosphate under no-tillage and rotovation tillage systems on crop production in a fine-loamy siliceous isohypothermic Typic Palendult were studied at Yurimaguas, Peru. A rotation of Al-tolerant cultivars of rice/rice/Vigna unguiculata was followed for 7 consecutive harvests. Grain yields increased with rotovation in the 1st crop, were not affected by tillage methods during the 2nd and 3rd crops, but decreased with rotovation from the 3rd to the 7th crops. Sechura phosphate rock at a soil pH of 4.5 was as effective as superphosphate in supplying available P. A total of 13.9 rice grain and 2.5 t of V. unguiculata seed/ha was produced in 7 harvests in newly cleared fields without lime or P application. There were significant responses to P in one rice crop and in both V. unguiculata crops. Rice yield did not generally respond to P. A single application of 22 kg P/ha was sufficient to produce 85% of the max. V. unguiculata yield for 2 years. The results with V. unguiculata indicate that broadcast phosphate rock is a good source of P for low-input systems on acid soils where acid-tolerant cultivars are used.